2008
DOI: 10.1097/hjh.0b013e3283018333
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory blood pressure as an independent determinant of brain atrophy and cognitive function in elderly hypertension

Abstract: In elderly hypertensive patients, absolute ambulatory systolic blood pressure level (particularly during sleep) and nocturnal dipping in systolic blood pressure were strong indicators of brain matter volume and cognitive function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
96
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(104 citation statements)
references
References 32 publications
4
96
1
3
Order By: Relevance
“…Among studies to date, van Boxtel et al 23 reported lower levels of cognitive function in non-dippers than in dippers, but did not separately analyze the effects of extreme dipping. Furthermore, Nagai et al 24 reported a positive association between the percent changes in nocturnal BP (as a numeric variable) and MMSE score in untreated hypertensive subjects, but again did not separately analyze the effects of an extreme decrease in BP. In this study, changes in nocturnal BP itself did not differ between MCI subjects and normal controls (Table 2) due to the high prevalence of MCI among not only non-dippers and risers but also extreme dippers (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among studies to date, van Boxtel et al 23 reported lower levels of cognitive function in non-dippers than in dippers, but did not separately analyze the effects of extreme dipping. Furthermore, Nagai et al 24 reported a positive association between the percent changes in nocturnal BP (as a numeric variable) and MMSE score in untreated hypertensive subjects, but again did not separately analyze the effects of an extreme decrease in BP. In this study, changes in nocturnal BP itself did not differ between MCI subjects and normal controls (Table 2) due to the high prevalence of MCI among not only non-dippers and risers but also extreme dippers (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…These authors also found that reduced total brain matter was involved in the association between blunted nocturnal BP changes and lower MMSE score. 24 Furthermore, in a recent longitudinal analysis found that increased white matter hyperintensities could be a predictor of progression from normal to MCI. 31 Association of silent cerebral infarctions with the development of MCI was also reported in another community-based longitudinal study.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports indicated that morning BP surge and morning hypertension increase the risk of organ damage and other conditions such as cardiovascular events, left ventricular hypertrophy, carotid intima-media thickness, and asymptomatic cerebral infarction, independent of 24-hour BP. 21,24,25 Increased nighttime BP is also associated with a higher cerebrovascular and cardiovascular event risk [26][27][28] and decreased cognitive and physical functions, 29,30 and vascular tissue damage has been shown to progress even if only nighttime BP is high, increasing the risk of cardiovascular events. 31 The importance of managing morning BP and nighttime BP is therefore well recognized.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Many prospective and cross-sectional observational studies have shown that hypertension is associated with cognitive decline in older persons. [5][6][7][8][9][10][11][12][13][14] Common to each of these studies, however, has been the relatively young age of the participants. The average age of these populations has been under 85 years; only a few studies have included individuals aged 90 years or above, and no studies have focused only on individuals aged 90 years or older.…”
Section: Introductionmentioning
confidence: 99%